FIRE flexible Intra-AS routing environment. - Partridge, Craig (Computer communication review.)
Current routing protocols are monolithic, specifying the algorithm used to construct forwarding tables, the metric used by the algorithm (generally some form of hop-count), and the protocol used to distribute these metrics as an integrated package. The Flexible Intra-AS Routing Environment (FIRE) is a link-state, intra-domain routing protocol that decouples these components. FIRE supports run-time-pro- grammable algorithms and metrics over a secure link-state distribution protocol. By allowing the network operator to dynamically reprogram both the information being advertised and the routing algorithm used to construct forwarding tables in Java, FIRE enables the development and deployment of novel routing algorithms without the need for a new protocol to distribute state. FIRE supports multiple concurrent routing algorithms and metrics, each constructing separate forwarding tables. By using operator-specified packet filters, separate classes of traffic are routed using completely different routing algorithms, all supported by a single routing protocol.